Analysis of Streptomyces ghanaensis ATCC14672 gene SSFG_07725 for putative γ-butyrolactone synthase - Kuzhyk, Yuriy; Mutenko, Halyna; Fedorenko, Victor; Ostash, Bohdan (Folia microbiologica, 2018)
Low molecular weight signaling compounds (LMWC) are important players in regulating various aspects of Streptomyces biology. Their exact roles in certain strain will ultimately depend on overall configuration of regulatory network and thus cannot be predicted on basis of in silico studies. Here, we explored S. ghanaensis gene SSFG_07725 (afsAgh) presumably involved in initial steps of formation of γ-butyrolactone LMWC. Disruption of afsAgh impaired aerial mycelium formation and increased the transcription of pleiotropic regulatory gene adpAgh, whereas level of moenomycin production remained virtually unaffected. We provide evidence that morphogenetic deficiency of afsAgh-minus mutant was caused by inability to produce diffusible LMWC. Possible links between γ-butyrolactone signaling and various aspects of S. ghanaensis biology are discussed.
Keywords: gama-butyrolakton; oligosacharidy; Bacterial Proteins; Oligosaccharides; mutace; 4-Butyrolactone; Mutation; Streptomyces; bakteriální proteiny